Norte mineiro peasant territory: settlement, resistance and fighting - Cunha, Maria das Graças Campolina (Revista Cerrados, 2013)
The aim of this study is to understand the dynamics that occurred in the North of Minas Gerais related to the settlement and permanence of rural populations in this region, as well as current strategies related to the guarantee of their territories in face of the expropriations suffered throughout its history. From the loss or reduction of their territories for the set up of developmentist projects conducted by the State, these relations are reaffi rmed through alliances signed with NGOs and civil institutions, strengthening them in the fi ght and conquest front of their territories.